Antimicrobial activity of medicinal plants used for urinary tract infections in pastoralist community in Ethiopia - Eshetu Gadisa; Elazar Tadesse (BMC, 2021)
Abstract Background Medicinal plants have wide medicament application used to prevent and management of many ailments. These plants are used for primary health care in pastoralist communities who are deprived of modern medical care. They possess extensive therapeutics bioactive coupled with varied chemical structures. However, scientific validation of efficacy and safety of plants used to treat the urinary tract infections haven't been fully exploited. The aim of this study was to evaluate antimicrobial activity and screening phytochemicals of medicinal plants used to treat urinary tract infections. Methods In-vitro experimental study was carried out to evaluate the antimicrobial effect and screening phytochemical of Rumex abyssinicus, Cucumis pustulatus, Discopodium penninervium, Lippia adoensis, Euphorbia depauperata, and Cirsium englerianum. Against drug resistance microbes. 80% methanol was used for extraction of the plant parts. The susceptibility tests were investigated using disc diffusion and broth micro-dilution methods. Results The majority of tested extracts showed antimicrobial activity on two or more drug-resistant bacteria with MIC value (1.0-128.0 μg/ml) and 9-27 mm inhibition zone in diameter. Extracts obtained from C.englerianum and E. depauperate showed more potent antibacterial activity on MRSA and Enterococcus faecalis with IZ 25 and 27 mm respectively. E. coli and K. pneumoniae were inhibited by those extracts with IZ ranging 9-25 mm and 11-27 mm respectively. E.faecalis and K. pneumoniae were more susceptible bacteria to the respective extracts. R. abyssinicus showed promising antifungal effect with had 21 mm IZ and MIC range 16-32 μg/ml on C.albicans. Alkaloids, flavonoids, phenolic and terpenoid were common phytochemical characterized in majority of screened plants. Conclusion Tested extracts exhibited significant antibacterial and antifungal activity. Hence, further structural elucidation of bioactive that inhibited the growth of microbes aforementioned plants may be used as precursors for the synthesis of new antibiotics in the future.